Afghanistan through women's eyes - Brown, Lisa; The Video Project (San Francisco, CA : The Video Project, 2001)
This video offers an intimate portrait of Afghanistan's silenced women as we see the conflict and history in Afghanistan through their eyes
This video is part of'Scared Sacred Project'
Production manager, Lisa Brown
Keywords: Women -- Afghanistan -- Social conditions; Afghanistan -- History